EDUCATIONAL LEADERSHIP IN DISRUPTIVE ERA: A FAITH CHALLENGE FACING INDONESIA - Gregorius Kukuh Nugroho (Lembaga Penelitian STKIP Widya Yuwana, 2019)
Higher education in Indonesia as an education service provider also inevitably has to change in the digital age. Higher education must be able to organize education by adjusting facilities according to the needs of students and the community, also in preparing leadership education. This era directs leadership in a new perspective. In a changing world, integrated strategic planning in line with institutional reforms in higher education and social responsibility dimensions is very important. Higher education institutions are an important component of economic and social infrastructure. Education is primarily a way to train students in the skills they will need as adults to get jobs, skills, and a good life. At the same time the formation of faith is a process of life. The next problem with catechesis is how catechetical institutions and catechists maintain faith in this era. Catechists must be educated to be leaders. Leadership education is very important in the global era. In a country where religious values ​​are highly respected, especially in Indonesia, catechists and catechetical institutions need to reflect more on the prophetic voice as a leader. As a leader, catechists have the ability to inspire, provide energy and to positively influence and motivate. Catechists and catechetical institutions must be involved in exploring, investigating, and experimenting with how things can be better than they are now.